2010
DOI: 10.1002/jrs.2609
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐enhanced Raman spectroscopy for quantitative measurement of lactic acid at physiological concentration in human serum

Abstract: Lactic acid is a simple and effective indicator for estimating physiological function. Rapid and sensitive detection of lactic acid is very useful in clinical diagnosis. However, the concentration of lactic acid in the physiological state is too low to be detected using traditional Raman spectroscopy. We applied silver colloidal nanoparticles-mediated surface-enhanced Raman spectroscopy (SERS) for rapid identification and quantification of lactic acid. The standard SERS spectra of lactic acid were defined and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 25 publications
1
20
1
1
Order By: Relevance
“…In addition to this, LA SERS spectrum shows strong Raman line at 1,390 and 823 cm −1 and weak lines at 528, 661, 745, 858, 928, 1,005, 1,040, 1,082, 1,138, 1,236, 1,454, 1,517, 1,601, 1,720, and 2,731 cm −1 . These spectral features are in good agreement with the earlier reports . The strong Raman line at 828 cm −1 is due to carbon and carboxylic group .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In addition to this, LA SERS spectrum shows strong Raman line at 1,390 and 823 cm −1 and weak lines at 528, 661, 745, 858, 928, 1,005, 1,040, 1,082, 1,138, 1,236, 1,454, 1,517, 1,601, 1,720, and 2,731 cm −1 . These spectral features are in good agreement with the earlier reports . The strong Raman line at 828 cm −1 is due to carbon and carboxylic group .…”
Section: Resultssupporting
confidence: 93%
“…These spectral features are in good agreement with the earlier reports. [48,51] The strong Raman line at 828 cm −1 is due to carbon and carboxylic group. [50] The intense band at 1,390 cm −1 is from carboxylic group which shows that LA was adsorbed on SERS chips via carboxylic group.…”
Section: Dft Raman and Sers Spectra Of Lamentioning
confidence: 99%
“…The results presented in this paper will help to further improve the sensitivity of NWERS sensors. Along with other integrated photonics functionalities, these on-chip Raman sensors can be employed in many interesting application such as the detection of VOCs [28] in ambient air or sensing of bio-analytes in physiological concentration [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Hsu et al . applied silver colloidal NPs‐mediated SERS for rapid identification and quantification of lactic acid . They showed that their silver colloidal NPs‐mediated SERS technique was able to detect lactic acid at physiological concentrations in blood.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%